Associations of Anemia With Outcomes in Patients With Spontaneous Intracerebral Hemorrhage: A Meta-Analysis - Zhang, Shuting; Pan, Xiaohua; Wei, Chenchen; Wang, Lu; Cheng, Yajun; Hu, Zhi; Dong, Wei; Liu, Ming; Wu, Bo (Frontiers in Neurology, 2019)
Background: Intracerebral hemorrhage (ICH) is a highly lethal disease without effective therapeutic interventions. Anemia is prevalent in neurocritical disease and correlated with higher mortality in the intensive care unit. However, there is a lack of evidence concerning the association between anemia and the clinical outcomes of ICH. Object: We aimed to assess the association between anemia and outcomes in patients with ICH. Methods: We systematically searched the Cochrane Library, MEDLINE, EMBASE and Web of Science from inception to November 2017. Eligible studies were cohort studies exploring the association between anemia and mortality or functional outcomes in patient with ICH. A Meta-analysis was performed, and heterogeneity was assessed using the I2 index. Sensitivity analyses were performed to account for heterogeneity and risk of bias. Effect estimates were combined using random effects model for mortality and poor outcomes. Results: We identified seven cohort studies with 7328 ICH patients, including 1546 patients with anemia. The meta-analysis revealed that anemia was associated with higher mortality OR=1.72 for 30-day mortality (95% CI 1.37 to 2.15; I2 =64%; low-quality evidence); OR=2.05 for 12-month mortality (95% CI 1.42 to 2.97; I2=82%; low-quality evidence) and an increased risk of poor outcome in patients with ICH OR=2.29 for 3-month outcome (95% CI 1.46 to 4.51; I2=91%; very low-quality evidence); OR=3.42 for 12-month outcome (95% CI 0.50 to 23.23; I2=96%; very low-quality evidence). Conclusions: Anemia on admission was associated with higher mortality and an increased risk of poor outcome in patients with ICH. However, the results were limited by the high heterogeneity of included studies. Prospective, multi-center or population-based, large sample cohort studies are needed in the future.